Juridical Analysis on Entrepreneurs’ Obligation of Effort to Prevent Termination of Employment - Budi Santoso (Universitas Airlangga, 2019)
This article aims to analyze the applicability of the employer's duty of care to prevent employment termination based on Article 15(1) Act No. 13 of 2003 on Labour, questioning if those obligations applied to all grounds and reasons resulting in termination of employment. To answer the objectives, this legal research uses the method of legislative approach by analyzing the available legal sources through systematic interpretation and legal argumentations. Relying on the result of the discussion, a conclusion is reached that employer's obligation of effort to prevent termination employment, as regulated under Article 151(1) UUK, is excluded when the employee is unable to perform its obligated duty after six months because he/she is entangled in criminal proceedings. If the Court decides the proceedings before the six months term ends and the employee is found to be guilty, then he/she is no longer the responsibility of the employer.